ANALISIS PERSEPSI MAHASISWA AKUNTANSI DALAM MEMILIH KARIR (Studi Empiris Mahasiswa Akuntansi S1 di Perguruan Tinggi di Semarang) - Nikho Averus; Herry Laksito (Diponegoro Journal of Accounting, 2015)
This  research  aim  to  identify  the  perception  of  accounting  students  about  the factors which differentiate of career selection as a accountan, public accountants, government accountants, private accountants, teachers accountants and . non-accountants The factors used a variable salary, professional training, professional recognition, social values, work environment, consideration of labor market need, personality and pride.The data was collect from surveyed respondents methods at several campuses in Semarang City ( UNDIP, UNIKA, UNNES, UDINUS,   and  STIE Bank BPD Jateng). Theamount of accounting students were 150 respondents. This research use SPSS version 20 and data analysis by ANOVA and Kruskal Wallis.The result shows that the difference of student’s perception about factors which influencing career choice are financial reward, professional training, professional confession,   social   values,   work   environment,   personality.   Meanwhile  there   is   no differences perception of consideration of labor market need and pride factor among students.